Service quality perception and customer satisfaction of AAO Global Insurance Brokers Sdn Bhd / Siti Nor Hidayah Ahmad Don - Ahmad Don, Siti Nor Hidayah (2010)
This study provides an analysis regarding customer satisfaction towards quality service provided by organization. The main objective of this project paper is to determine the level customer satisfaction towards quality service perception that provided by AAO Global Insurance Brokers Sdn Bhd by examining the SERVQUAL scale that consist of five factors, which are tangible, reliability, responsiveness, assurance and empathy. This research is focusing on clients that consume the service provided by AAO Global Insurance Brokers Sdn Bhd. The theoretical framework of this study consists of the factors or dimensions that influence the customer satisfaction. The factors are adapted from SERVQUAL, which is an instrument for measuring quality service developed by Zeithaml, Parasuraman & Berry (1991). From this study, AAO Global Insurance Brokers Sdn Bhd is able to identify the problems which rely on the level of customer satisfaction of AAO Global Insurance Brokers, the level of quality service provided by AAO Global Insurance Brokers and the relationship between the service quality perception and the customer satisfaction. Data collections are gathering from the observations and distributing the questionnaire. This project paper consisting of four chapters, which in chapter one consist of introduction and background of the research, chapter two consist of literature review, chapter three is research methodology and design and chapter four is result, conclusion and suggestions.